Invincible - Core, Ericson; Wahlberg, Mark, 1971-; Kinnear, Greg, 1963-; Banks, Elizabeth, 1974-; Conway, Kevin; Rispoli, Michael; Isham, Mark.; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Walt Disney Home Entertainment, Distributed by Buena Vista Home Entertainment, 2006)
Vince Papale is a down-on-his-luck substitute teacher in Philadelphia who, at the age of 30, was out of work, abandoned by his wife, and biding time as a part-time bartender when he decides to answer an open call for tryouts on the Philadelphia Eagles NFL football team in 1976. Going with his gut instinct, new coach Dick Vermeil rewards Papale's diligent efforts with a place on the team.
Title from container.
Widescreen.
Special features: 'Becoming Invincible : the Vince Papale story'; Vince Papale, producer Mark Ciardi and writer Brad Gann audio commentary; director Ericson Core and editor Jerry Greenberg commentary.
Director of photography, Ericson Core ; editor, Gerald B. Greenberg ; music, Mark Isham ; costume designer, Susan Lyall ; production designer, Sarah Knowles.
Mark Wahlberg, Greg Kinnear, Elizabeth Banks, Kevin Conway, Michael Rispoli, Kirk Acevedo, Dov Davidoff, Michael Kelly, Sal Darigo, Nicoye Banks.
MPAA rating: PG; for sports action and some mild language.
Keywords: Papale, Vince -- Drama; Philadelphia Eagles (Football team) -- Drama; Football players -- Pennsylvania -- Philadelphia -- Drama; Feature films; Films for the hearing impaired